Government size and economic growth: some evidence from a market price approach - Erkki Koskela; Matti Virén (Bank of Finland, 1990)
This paper presents a simple model of aggregate demand in current market prices, in which public sector employment affects aggregate (and private) demand via the total output, the lump-sum taxes and the valuation of public sector production. Whlle the last effect is positive for aggregate demand, the other two effects are ambiguous a priori so that the total effect remains indeterminate. On the other hand, the relationshi'p between public sector employment and private output (and demand) is quite likely sensitive to and might depend inversely on the size of the public sector. Empirical results using data from 19 OECD countries over the period 1960 - 1987 indicate that there is practically no within-country relationship between public sector employment and private sector output over time, while there seems to be some, though weak, evidence in favour of the hypothesis that the effect of the public sector employment on private sector output depends inversely on the size of the publie sector across countries.
URN:NBN:fi:bof-201807311797
Keywords: 330